Comparison of Host Expression Systems used for Efficient Recombinant Proteins Production: Host Expression System for Recombinant Proteins Production - Sania Sahreen,; Sundas Sharif,; Hamna Ahmad,; Mukhtar, Hamid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The marvels of DNA recombination technology have revolutionized the field of biotechnology. Several hormones, antibody subunits, vaccines, enzymes, and interferons are being produced at the industrial level, in suitable expression systems, under optimized conditions. For recombinant protein production, a range of expression systems are available such as bacteria, yeast, fungi, plant cells, insects and animal cells, etc. Each recombinant protein has different nature due to which it requires different challenges regarding the expression system and production conditions. Every expression system has its advantages and limitations on the basis of which it can be considered or rejected for a particular protein production. Therefore, it is very significant to investigate the potential and limitations of several expression systems to choose the suitable one for particular protein production at an industrial scale. The optimization criteria of an expression system is evaluated on several factors such as productivity, efficiency, physiological characteristics, total cost, safety, convenience, and down-streaming conditions. Escherichia coli and Saccharomyces cerevisiae remained the organisms of choice to produce recombinant proteins for a long time, but now several other microorganisms are also being targeted to evaluate their efficiency toward recombinant protein production. Prokaryotic expression systems can be used to produce eukaryotic proteins as well however, the use of a eukaryotic expression system is preferable because it retains the structural, functional, and regulatory properties of therapeutic proteins. This review illustrates a brief view of a variety of expression systems, their efficiency, and limitations in recombinant protein production.